De Novo Truncating Mutations in the Kinetochore‐Microtubules Attachment Gene CHAMP1 Cause Syndromic Intellectual Disability. Issue 4 (4th February 2016) - Isidor, Bertrand; Küry, Sébastien; Rosenfeld, Jill A.; Besnard, Thomas; Schmitt, Sébastien; Joss, Shelagh; Davies, Sally J; Roger Lebel, Robert; Henderson, Alex; Schaaf, Christian P.; Streff, Haley E.; Yang, Yaping; et al.
Abstract : By trio‐based whole‐exome sequencing in six unrelated non‐consanguineous families we identified a syndromic form of intellectual disability with impaired speech caused by de novo truncating mutations in CHAMP1 . This gene encodes a protein involved in microtubule‐kinetochore attachment, whose mutations induce its delocalization from chromatin and its inability to bind to its direct partners, POGZ and HP1. ABSTRACT: A rare syndromic form of intellectual disability with impaired speech was recently found associated with mutations in CHAMP1 (chromosome alignment‐maintaining phosphoprotein 1), the protein product of which is directly involved in microtubule‐kinetochore attachment. Through whole‐exome sequencing in six unrelated nonconsanguineous families having a sporadic case of intellectual disability, we identified six novel de novo truncating mutations in CHAMP1 : c.1880C>G p.(Ser627*), c.1489C>T; p.(Arg497*), c.1876_1877delAG; p.(Ser626Leufs*4), c.1043G>A; p.(Trp348*), c.1002G>A; p.(Trp334*), and c.958_959delCC; p.(Pro320*). Our clinical observations confirm the phenotypic homogeneity of the syndrome, which represents therefore a distinct clinical entity. Besides, our functional studies show that CHAMP1 protein variants are delocalized from chromatin and are unable to bind to two of its direct partners, POGZ and HP1. These data suggest a pathogenic mechanism of the CHAMP1 ‐associated intellectual disability syndrome mediated by direct interacting partners of CHAMP1, several of which are involved in chromo/kinetochore‐related disorders.